The cut-offs for kappa/lambda ratio in bone marrow immunohistochemistry for the diagnosis of multiple myeloma. Issue 1 (1st January 2020) - Warnnissorn, Naree; Treetipsatit, Jitsupa; Limvorapitak, Wasithep
ABSTRACT: Objective: The previously reported kappa/lambda ratio cut-offs for plasma cell clonality by immunohistochemistry were in different values. This study aimed to identify the cut-offs with the highest accuracy for the diagnosis of multiple myeloma. Methods: Bone marrow specimens consecutively recruited between January 2011 and March 2019. The patients were at least 18 years old with clinical suspicion of multiple myeloma and had bone marrow plasma cell ≥10% by CD138 immunohistochemistry. The index test was immunohistochemical stains for plasma cell kappa/lambda ratio. The reference standard to classify as multiple myeloma required meeting any of the following (1) kappa/lambda ratio ≤1/16 or ≥16, (2) abnormal plasma cell morphology, and (3) monoclonal immunoglobulin. Results: From 147 specimens (70 multiple myelomas and 77 reactive plasmacytosis), our cut-offs kappa/lambda ratio for light chain restriction at ≤1/7 or ≥9 yielded an area under the receiver operating characteristic curve of 1.0000 while ≤1/16 or ≥16 yielded 0.9643 ( p -value 0.0212). Conclusion: The cut-offs for kappa/lambda ratio at ≤1/7 or ≥9 for diagnosis of multiple myeloma yielded the highest diagnostic accuracy. The suggested cut-offs could be of potential value in resource-limited laboratories.